Selecting species for vineyard inter-row vegetation cover requires consideration of microenvironmental conditions. - Cristina Pornaro; Stefano Macolino (PLoS ONE)
Vegetation between the vineyard rows is considered a service crop due to the many ecosystem services it provides. These benefits mostly depend on the species or mixtures selected. Vineyard can directly impact the microclimate by modifying the amount of energy available for the herbaceous layer affecting parameters such as soil temperature and moisture. Our hypothesis was that changes in inter-row vegetation composition change are driven by micronvironmental condition. A field trial was conducted in a vineyard of Cabernet Sauvignon Vitis vinifera L. cultivars, managed organically, in north-eastern Italy, where three blends of grass species (Shedonorus arundinaceus, Lolium perenne, and Festuca rubra) and two grass-legume mixtures were grown in the inter-rows. These were compared with spontaneous vegetation and bare soil regularly tilled. Each type of inter-row cover, including resident vegetation, was subjected to mulching and non-mulching treatments. The study aimed at evaluate the response to microenvironmental conditions of seeded species, mixtures, and spontaneous vegetation in the inter-row spaces of the vineyard. The relative abundance of each species was recorded during the spring after seeding (2019) and during the spring of 2020. Soil compaction, soil temperature, and soil moisture were measured during spring 2020. A significant change in botanical composition occurred two years after seeding according to the type of vegetation. However, some species remained in or spread to specific sections of the inter-row. Lolium perenne was more abundant in the southwest and northeast sections of the inter-row, where there was greater soil compaction. Similarly, the abundance of weed species such as Cynodon dactylon, Setaria italica, and Plantago lanceolata, was related to microenvironmental conditions. Seeded (Festuca rubra) or weed species (C. dactylon, Erigeron annuus, and Lactuca serriola) appear to benefit from soil moisture and higher temperatures. Therefore, microenvironment adaptability is the primary factor to consider when selecting species for vineyard inter-row cover.